2019
DOI: 10.3390/w11040708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drying and Re-Wetting on Litter Decomposition and Nutrient Recycling: A Manipulative Experiment

Abstract: Climate change and water abstraction may change stream flow from perennial into intermittent lotic systems, modifying their abiotic and biotic benthic environment and impacting ecosystem processes such as nutrient turnover. We conducted a microcosm experiment to investigate the interactive effect of water intermittency, macrofauna and leaf size (Populus nigra leaves) on nutrient mineralization and recycling. Leaf disks (1 or 5 cm diameter) were incubated for 40 days with or without the leaf-consumer, Potamophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Most other studies have found a slower breakdown of leaves in streams that are dry, whether intermittent or ephemeral. Invertebrates that consume leaves, shredders, often contribute significantly to leaf breakdown, so if these animals are lost upon drying, rates will be much lower (Datry et al, 2011;Ledger, Harris, Armitage, & Milner, 2012;Palmia et al, 2019). Microbes, the other biological player in The control treatment leaves remained immersed in the stream for the 2 weeks of treatments; the drying treatments were exposed to air for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Most other studies have found a slower breakdown of leaves in streams that are dry, whether intermittent or ephemeral. Invertebrates that consume leaves, shredders, often contribute significantly to leaf breakdown, so if these animals are lost upon drying, rates will be much lower (Datry et al, 2011;Ledger, Harris, Armitage, & Milner, 2012;Palmia et al, 2019). Microbes, the other biological player in The control treatment leaves remained immersed in the stream for the 2 weeks of treatments; the drying treatments were exposed to air for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, are the organic matter pool and its macromolecular composition, that may vary among canals and among sites, the sediment permeability and the length of air exposure period. We speculate that increased exposure periods to the atmosphere may affect microbial communities and related activity, organic matter aging and sediment properties, with implication for fluxes (Amalfitano et al 2008;Ylla et al 2010;Palmia et al 2019).…”
Section: Irrigation Canals As Model Systems To Study the Effects Of Desiccation On C Turnover And Co 2 Emissionmentioning
confidence: 98%
“…In general, metabolic rates should decrease along with the time of exposure due to progressive depletion of the more labile organic matter fraction or the increase of C:N ratios in the residual litter (Palmia et al 2019). As during 2019 the 5 canals were dried out at the beginning of October and samplings occurred during the last 2 weeks of October, sediments were exposed for a period comprised between 2 and 4 weeks.…”
Section: Irrigation Canals As Model Systems To Study the Effects Of Desiccation On C Turnover And Co 2 Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is an urgent need to understand the effects that climate change, reduced water availability, and hydrological intermittency on river ecology. Studies focus on the dynamics of macrofauna and on the implications for organic matter processing and downstream nutrient transport (Corti et al, 2011; Palmia et al, 2019). They also analyze the possible implications for river groundwater interactions, hatch success of crustaceans, fish, and amphibians using riverbed for eggs deposition and sediment transport (Uys & O'keeffe, 1997; Vander Vorste et al, 2020; Whiles & Goldowitz, 2001).…”
Section: Introductionmentioning
confidence: 99%